Evaluation of β-glucan particles as dual-function carriers for poorly soluble drugs - Šalamúnová, Petra; Saloň, Ivan; Ruphuy, Gabriela; Kroupová, Jiřina; Balouch, Martin; Hanuš, Jaroslav; Štěpánek, František (European journal of pharmaceutics and biopharmaceutics, 2021)
Yeast glucan particles are porous polysaccharide cell walls extracted from Saccharomyces cerevisiae. Being mildly immunogenic, they are efficiently phagocytosed and have therefore been proposed as possible vehicles for drug delivery. Using curcumin as a model poorly water-soluble drug, a systematic comparison of three different physical loading methods - incipient wetness impregnation, slurry evaporation, and spray drying - was carried out and their influence on the particle morphology, encapsulation efficiency, amorphous drug content and release kinetics was evaluated. It was found that yeast glucan particles can contain up to 30% wt. of curcumin in the amorphous form when prepared by slurry evaporation. The dissolution of curcumin from glucan particles lead to a supersaturated solution in asimilar way as amorphous solid dispersions do, despite the fact that glucan particles themselves do not dissolve. Bi-phasic dissolution tests revealed up to 4-fold acceleration of curcumin dissolution rate from amorphous glucan particles compared to its crystalline form. Crucially, glucan particles were shown to retain the ability to be recognised and phagocytosed even after drug encapsulation.
Keywords: farmaceutická chemie; krystalizace; Drug Carriers; Crystallization; beta-glukany; beta-Glucans; rozpustnost; Drug Delivery Systems; kurkumin; Drug Liberation; uvolňování léčiv; Curcumin; Kinetics; lékové transportní systémy; voda; Drug Compounding; Solubility; nosiče léků; příprava léků; Chemistry, Pharmaceutical; Water; kinetika